The effects of religiosity and external environment on voluntary tax compliance - Mohdali, Raihana; Pope, Jeffrey (Brookers Thomson, 2012)
This article aims to explore the role of religious values held by taxpayers, as well as taking into account the external environment; namely government, the tax authority and society in enhancing voluntary tax compliance. Employing a self-administered survey (both drop-off and online), this mixed mode methods study involved approximately 300 individual taxpayers in Malaysia. Religiosity is found to have a positive influence in encouraging taxpayers’ willingness to comply with tax laws in Malaysia. In addition, taxpayers’ perceptions towards the government and taxpayers’ interactions with the tax authority appear to have a significant impact on voluntary tax compliance. One of the possible explanations for these results is the strong religious values held by many Malaysians. Other reasons include the democratic rights given to Malaysians and professional relationships between the Inland Revenue Board of Malaysia (IRBM)1 and taxpayers.